PENGARUH MATA PELAJARAN BISNIS RITEL, MOTIVASI BELAJAR, DAN KECERDASAN ADVERSITAS TERHADAP KESIAPAN BERWIRAUSAHA PADA SISWA KELAS XII JURUSAN BISNIS DARING DAN PEMASARAN SMK NEGERI 13 MEDAN - Samuel Karip Tambunan; Pasca Dwi Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to examine the influence of retail business subjects, learning motivation, and adversity quotient on the entrepreneurial readiness of XII grade students majoring in online business and marketing at SMK Negeri 13 Medan. The population for this study consists of 33 students. This type of research is ex- post facto and the sampling technique used in the research is total sampling, totaling 33 students. The data collection instruments used are retail business subjects by taking scores, learning motivation with 15 statement items, adversity quotient with 15 statement items, and entrepreneurial readiness with 15 statement items. The data analysis techniques used in this study involve classical assumption testing, multiple linear regression, and hypothesis testing, measuring how much influence retail business subjects, learning motivation, and adversity quotient have on entrepreneurial readiness. This research shows that the subject of retail business, learning motivation, and adversarial intelligence have a significant and positive effect on the entrepreneurial readiness of grade XII students in the online business and marketing program at SMK Negeri 13 Medan.